Realization of Speech Acts of Suggestion by EFL Learners of Universitas Negeri Semarang - Shofwan, Muh Imam; Mujiyanto, Januarius (English Education Journal, 2018)
This research is a pragmatic study about realization of speech acts of suggestion by EFL learners of Universitas Negeri Semarang. The primary objectives are to explain how EFL learners of Universitas Negeri Semarang realize the speech acts of suggestion, their realization of direct strategy, conventionalized form, indirect and the use of mitigation devices to produce suggestions. To this end, the data were gathered through Discourse Completion Task (DCT) and roleplay. The data were analyzed using Martinez-Flor’s (2005) taxonomy. 20 undergraduate students of EFL learners of Universitas Negeri Semarang were the respondents. The result showed that students realized their suggestion using conventionalized form more frequently than other strategies. The direct strategy was performed using performative verb more often. Conventionalized was form frequently realized by using modal should and need. Indirect strategy was performed by using hints more than impersonal. Moreover, the use of mitigating devices to redress the threatening toward the hearers’ face performed frequently by opener. It is expected that the findings of this study could encourage English language teachers particularly in teaching speech act of suggestion by using the most suitable approach.